Fuzheng Huayu tablets for treating pulmonary fibrosis in post-COVID-19 patients: a multicenter, randomized, double-blind, placebo-controlled trial - Jing, Fei; Wang, Wei; Ke, Jia; Huang, Tingrong; Jiang, Bo; Qiu, Qiwu; Huang, Jihan; Zhan, Songhua; Zhang, Wei; Wu, Hui; Su, Wen; Feng, Jiawen; et al. (Frontiers in Pharmacology, 2025)
BackgroundEffective therapies for pulmonary fibrosis caused by coronavirus disease (COVID-19) and other etiologies are lacking. Our previous studies demonstrated that Fuzheng Huayu tablet (FZHY), a traditional Chinese medicine known for its anti-liver fibrotic properties, can improve lung function in patients with chronic obstructive pulmonary disease and attenuate bleomycin-induced pulmonary fibrosis in rats.PurposeThis study aimed to evaluate the efficacy and safety of FZHY in post-COVID-19 pulmonary fibrosis.MethodsA multi-center, randomized, double-blind, placebo-controlled clinical trial was conducted to evaluate the efficacy of a 24-week treatment with FZHY, combined with vitamin C and respiratory function rehabilitation, for treating pulmonary fibrosis in discharged convalescent COVID-19 patients. The primary outcome was the regression rate of pulmonary fibrosis assessed by the high-resolution computed tomography scores and lung function improvement (forced vital capacity [FVC], forced expiratory volume in one second [FEV1], and FEV1/FVC) after 24 weeks. Secondary outcomes included the 6-min walk distance, improvement in pulmonary inflammation, clinical symptoms, and quality of life.ResultsThis study included 142 patients, who were randomized to the FZHY (n = 72) and placebo groups (n = 70). By week 24, the regression rates of pulmonary fibrosis in the FZHY and placebo groups were 71.2% and 49.2%, respectively (p = 0.01). Limited spirometry data revealed higher FEV1/FVC in the FZHY group than in the placebo group at week 8 ([87.7 ± 7.2] % vs. [82.7 ± 6.9] %; p = 0.018). The regression rates in pulmonary inflammation in the FZHY and placebo groups were 83.8% and 68.8%, respectively (p = 0.04). At week 4, the increase in 6-min walking distance was greater in the FZHY group than in the placebo group ([41.4 ± 64.1] m vs. [21.8 ± 50.3] m; p = 0.05). However, no significant differences were observed between the groups in the improvement rate of clinical symptoms, quality of life-BREF, patient health questionnaire-9, or generalized anxiety disorder-7 scores (p > 0.05). No drug-related adverse events were reported in the FZHY group.ConclusionFZHY attenuates post-COVID-19 pulmonary fibrosis, with good safety profiles.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04279197, identifier NCT04279197.